PENGARUH ORIENTASI PASAR DAN INOVASI JASA TERHADAP KINERJA PEMASARAN MELALUI KEUNGGULAN BERSAING PADA HOTEL NON BINTANG DI KOTA SEMARANG - Bernadeta Dewi Kusuma Jat; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
Marketing performance reflects the company's success in the face of stiff competition. One of the factors that affect the marketing performance is competitive advantage. Competitive advantage itself is affected by market orientation and services innovation. Non-star hotels in Semarang has a low occupancy rate in conditions of intense competition. The purpose of this study was to determine the effect of market orientation and service innovation to marketing performance through competitive advantage at the non-star hotel in the city of Semarang. The study uses a quantitative approach. This type of research is explanatory. With the number of respondents are 50 hotels. Data were obtained through a questionnaire instrument with tools of analysis, SPSS version 17.0. The results showed that the market orientation and service innovation affect the marketing performance through competitive advantage. Market orientation has a greater influence than the service innovation. Competitive advantage is a full mediating variables for market orientation and services innovation. Suggestions for the company to further enhance attention to services innovation based on market information obtained so that the marketing performance of non-star hotels in Semarang can be improved.